Congenital clubfoot: parents’ considerations about the disease and its treatment - Souza Júnior, Eli Ávila; Simões, Guilherme Ferreira; Nunes, Sabrina Versuti; Gomes, Davi Coutinho Fonseca Fernandes; Campos, Túlio Vinicius de Oliveira; Andrade, Marco Antônio Percope de (Scientific Journal of the Foot & Ankle, 2018)
Objectives: To learn parents' impressions regarding the diagnosis of congenital clubfoot and its treatment. This information may favor persistence with treatment, breakdown of taboos and therapeutic success. Methods: A qualitative and descriptive study with 10 parents whose children have congenital clubfoot. The tabulation of the data occurred through the use of three methodological figures: central idea, key expressions and collective subject discourse. Results: When asked about impressions generated when their child was diagnosed with congenital clubfoot, 70% reported feelings of sadness, fright and worry, and only 30% showed a calm acceptance of the diagnosis, devoid of fear and worry. When asked about the treatment that was being done, 100% of the parents showed optimism and satisfaction with the results presented, 40% mentioned the comfort level brought by the therapeutic methods and 20% mentioned the importance of the involvement of the entire health team in the therapeutic approach. Conclusion: Fear and concern were common feelings, which improved with the best elucidation by the health team regarding the disease. Regarding therapy, the parents' satisfaction was unanimous. Level of Evidence V, Expert Opinion.